Antimicrobial resistance in the practice of primary care physicians: antimicrobial therapy - Laudy-Wiaderny, Hanna; Nitsch-Osuch, Aneta (Family Medicine & Primary Care Review, 2025)
Rational antibiotic therapy represents one of the crucial efforts to combat the rising resistance of pathogens to antimicrobial drugs. The principal characteristics of this treatment approach are its high efficacy, patient safety, low cost, convenient dosing, and the minimization of the risk of resistance development. Specific consideration is required regarding antibiotic therapy during pregnancy and lactation. The antibiotics that are considered safe during pregnancy are mainly penicillins and cephalosporins. It is contraindicated to use aminoglycosides or tetracyclines during this period. A greater range of safe preparations is available during lactation. In the event of uncertainty regarding drug safety during these periods, numerous databases are available to assist with the selection of the most appropriate therapeutic option. A crucial aspect of efficacious antibiotic therapy is the monitoring of treatment outcomes, which encompasses both clinical assessment and, when indicated, supplementary testing. It is also important to take into account the potential adverse effects of the medications being used. A noteworthy phenomenon observed in primary care is the carrier of pathogens. In most cases, these patients do not receive treatment unless their individual circumstances necessitate it. Infection prevention, which entails immunization and patient education, represents a vital strategy for reducing the need for antibiotics. Regular monitoring and strict adherence to antibiotic therapy can markedly enhance treatment efficacy and mitigate the risk of complications. This is the third article in a series addressing antibiotic resistance issues from the perspective of family medicine practice.